Relationship Types Of Parenting Styles In Providing Smartphone With The Risk Of Attention Deficit And Hyperactivity Disorder In Preschool Children - Dian Fitria Kurniawati; Ahmad Suryawan; Astika Gita Ningrum (Poltekkes Kemenkes Yogyakarta, 2023)
Attention deficit and hyperactivity disorder (ADHD) is a childhood disorder characterized by inattention, hyperactivity, and impulsivity, particularly in children under seven years old. Addiction to electronic media, such as smartphones, is one of the causes. The way parents provide smartphones to their children can have an effect on the impact of smartphone use. The purpose of this study is to investigate the impact of parenting styles and the risk of attention deficit and hyperactivity disorder in preschool children. This study employs an observational analytic methodology with a cross-sectional approach. The data was analyzed using univariate and bivariate methods, as well as the chi-square test. Conforming to the results, democratic parenting was the most common kind of parenting in children who did not have ADHD, with 38 respondents (92.7%), and authoritarian parenting was the least common, with 17 respondents (89.5%). Meanwhile, for children at risk of ADHD democratic parenting is the most common parenting style, with 3 respondents (7.3%), while authoritarian parenting is the least common, with 2 respondents (10.5%). The chi-square correlation test revealed no connection between the styles of parenting in providing smartphones and the risk of attention deficit and hyperactivity disorder in preschool children (p-value 0.676 > 0.05). The appropriate parenting style in handing smartphones to children from both parents and the closest people is very significant because it is related to the bad influence that children gain from using smartphones.